SAT0389 Color or power doppler - which is more sensitive and do machine settings matter?. (23rd January 2014) - Torp-Pedersen, S.; Szkudlarek, M.; Ellegaard, K.; D'Agostino, M.-A.; Iagnocco, A.; Naredo, E.; Balint, P.; Wakefield, R.; Torp-Pedersen, A.; Christensen, R.; Terslev, L.
Abstract : Background: The sensitivity of Doppler to detect slow blood flow in inflamed joints is of utmost importance. This may be influenced by factors such as Doppler modality, machine and settings. Power Doppler (PD) is widely regarded the most sensitive Doppler modality, however, on some machines color Doppler (CD) appears more sensitive. The effect of sensitivity (image acquisition) on the subsequent scoring (image evaluation) is important for multicenter studies because of variability in machines, modalities, and settings. Objectives: 1: To determine which Doppler modality was most sensitive – CD or PD - by assessing flow in the dorsal central wrist joint in patients with RA. 2: If adjusting factory settings (FS) for CD and PD influenced the sensitivity positively and 3: If a variation in machines, Doppler modality, and Doppler settings affected the Doppler scoring. Methods: Six different ultrasound machines from Esaote, General Electric, Philips, and Siemens were used. On each machine, the FS for superficial musculoskeletal scanning was used for both Doppler modalities. The settings were adjusted for increased Doppler sensitivity (1) and these settings were saved as study settings (SS). 11 RA patients with wrist involvement were scanned on the 6 machines each with 4 settings generating 264 Doppler images for scoring using grading 0-3 (2) and color fraction (CF) (3). Doppler sensitivity was measured with CF – higher CF indicated higher sensitivity. Results: Using both scoring systems, PD was more sensitive on Esaote MyLab 70, Siemens S2000 and GE P6, whereas CD was more sensitive on GE E9, Philips IU22 and GE P5. This was the case both with FS and SS. There was a mean increase in Doppler sensitivity of 68% (range 0-156) when SS were applied. Over the 6 machines, 2 Doppler modalities, and 2 settings, 7 patients varied between grades 0 and 3 with the other 4 patients between grades 0 and 2. Conclusions: The most sensitive Doppler modality for slow flow is machine dependable. On half of the machines, PD was more sensitive than CD – the other half vice versa. By optimizing Doppler settings, sensitivity was increased up to 156% (mean 68%). The effect of using different machines, Doppler modalities, and settings has a considerable influence on the quantification of inflammation in RA patients and this must be taken into account in multicenter studies. References: Settings and artefacts relevant in colour/power Doppler ultrasound in rheumatology. ARD 2008;67(2):143-9. Interobserver agreement in ultrasonography of the finger and toe joints in rheumatoid arthritis. Arthritis Rheum. 2003;48(4):955-62. Quantitative ultrasonography in rheumatoid arthritis: evaluation of inflammation by Doppler technique. ARD 2001;60(7):690-3. Disclosure of Interest: S. Torp-Pedersen Grant/Research support from: The study was supported by a grant from General Electric, M. Szkudlarek: None Declared, K. Ellegaard: None Declared, M.-A. D'Agostino: None Declared, A. Iagnocco: None Declared, E. Naredo: None Declared, P. Balint: None Declared, R. Wakefield: None Declared, A. Torp-Pedersen: None Declared, R. Christensen: None Declared, L. Terslev: None Declared